Immunocompetent 3D Model of Human Upper Airway for Disease Modeling and In Vitro Drug Evaluation - Harrington, Helen; Cato, Paul; Salazar, Fabian; Wilkinson, Malcolm; Knox, Alan; Haycock, John W.; Rose, Felicity R.A.J.; Aylott, Jonathan W.; Ghaemmaghami, Amir M. (American Chemical Society, 2014)
The development of more complex in vitro models for the assessment of novel drugs and chemicals is needed because of the limited biological relevance of animal models to humans as well as ethical considerations. Although some human-cell-based assays exist, they are usually 2D, consist of single cell type, and have limited cellular and functional representation of the native tissue. In this study, we have used biomimetic porous electrospun scaffolds to develop an immunocompetent 3D model of the human respiratory tract comprised of three key cell types present in upper airway epithelium. The three cell types, namely, epithelial cells (providing a physical barrier), fibroblasts (extracellular matrix production), and dendritic cells (immune sensing), were initially grown on individual scaffolds and then assembled into the 3D multicell tissue model. The epithelial layer was cultured at the air–liquid interface for up to four weeks, leading to formation of a functional barrier as evidenced by an increase in transepithelial electrical resistance (TEER) and tight junction formation. The response of epithelial cells to allergen exposure was monitored by quantifying changes in TEER readings and by assessment of cellular tight junctions using immunostaining. It was found that epithelial cells cocultured with fibroblasts formed a functional epithelial barrier at a quicker rate than single cultures of epithelial cells and that the recovery from allergen exposure was also more rapid. Also, our data show that dendritic cells within this model remain viable and responsive to external stimulation as evidenced by their migration within the 3D construct in response to allergen challenge. This model provides an easy to assemble and physiologically relevant 3D model of human airway epithelium that can be used for studies aiming at better understanding lung biology, the cross-talk between immune cells, and airborne allergens and pathogens as well as drug delivery.